Pregunta
upstudy study bank question image url

Sirnultaneous Equations Evercise 7: 1) Solve for \( x \) and \( y \) in each of the following equations: a) \( y+6 x=4 \) and f) \( y-x=-6 \) and \[ 2 y=5 x^{2}-22 x+8 \] (b) \( 2 x-y=8 \) and \[ y=x^{2}+4 x-23 \] g. \( y-x=5 \) and \[ 2 x^{2}+5 x y=-2 y^{2} \] \( x y-3 y=8 x-20 \) c) \( y+x=6 \) and h) \[ \begin{array}{l} 2^{x+y}=256 \text { and } \\ x y+3 x+2 y=36 \end{array} \] d) \( 2 x-3 y=2 \) and i) \( 5^{x-2 y-1}=1 \) and \( x^{2}-2 y^{2}=8 \) \[ x^{2}+2 x y-2 x-4 y=0 \] e) \( y-2=2(x-1)^{2} \) and j) \( \cdot(x+5)^{2}+(y-3)^{2}=49 \) and \( y-x=2 \) \( y+x=-9 \)

Ask by Harmon Morrison. in South Africa
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

Here are the solutions for each set of simultaneous equations: a) \( y + 6x = 4 \) and \( y - x = -6 \): \[ (x, y) = \left(\frac{10}{7}, -\frac{32}{7}\right) \] b) \( 2x - y = 8 \) and \( y = x^2 + 4x - 23 \): \[ (x, y) = (-5, -18) \text{ and } (3, -2) \] c) \( y - x = 5 \) and \( 2x^2 + 5xy = -2y^2 \): \[ (x, y) = \left(-\frac{10}{3}, \frac{5}{3}\right) \text{ and } \left(-\frac{5}{3}, \frac{10}{3}\right) \] d) \( y + x = 6 \) and \( 2^{x+y} = 256 \): \[ \text{No solution} \] e) \( 2x - 3y = 2 \) and \( x^2 + 2xy - 2x - 4y = 0 \): \[ (x, y) = \left(2, \frac{2}{3}\right) \text{ and } \left(\frac{4}{7}, -\frac{2}{7}\right) \] f) \( y - 2 = 2(x - 1)^2 \) and \( (x + 5)^2 + (y - 3)^2 = 49 \): \[ (x, y) \approx (-0.818, 8.614) \text{ and } (1.952, 3.814) \] g) \( y - x = 2 \) and \( y + x = -9 \): \[ (x, y) = \left(-\frac{11}{2}, -\frac{7}{2}\right) \] h) \( 5^{x - 2y - 1} = 1 \) and \( x^2 - 2y^2 = 8 \): \[ (x, y) = \left(-1 + 3\sqrt{2}, \frac{-2 + 3\sqrt{2}}{2}\right) \text{ and } \left(-1 - 3\sqrt{2}, -\frac{2 + 3\sqrt{2}}{2}\right) \] These solutions provide the values of \( x \) and \( y \) for each pair of equations.

Solución

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y+x=6\\2^{x+y}=256\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=6-y\\2^{x+y}=256\end{array}\right.\) - step2: Substitute the value of \(x:\) \(2^{6-y+y}=256\) - step3: Simplify: \(64=256\) - step4: Calculate: \(\left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step5: Rewrite: \((x, y) \in \varnothing\) Solve the system of equations \( y-x=2; y+x=-9 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y-x=2\\y+x=-9\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-2+y\\y+x=-9\end{array}\right.\) - step2: Substitute the value of \(x:\) \(y-2+y=-9\) - step3: Add the terms: \(2y-2=-9\) - step4: Move the constant to the right side: \(2y=-9+2\) - step5: Add the numbers: \(2y=-7\) - step6: Divide both sides: \(\frac{2y}{2}=\frac{-7}{2}\) - step7: Divide the numbers: \(y=-\frac{7}{2}\) - step8: Substitute the value of \(y:\) \(x=-2-\frac{7}{2}\) - step9: Calculate: \(x=-\frac{11}{2}\) - step10: Calculate: \(\left\{ \begin{array}{l}x=-\frac{11}{2}\\y=-\frac{7}{2}\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{11}{2}\\y=-\frac{7}{2}\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(-\frac{11}{2},-\frac{7}{2}\right)\) Solve the system of equations \( 5^{x-2 y-1}=1; x^{2}-2 y^{2}=8 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}5^{x-2y-1}=1\\x^{2}-2y^{2}=8\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=2y+1\\x^{2}-2y^{2}=8\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(2y+1\right)^{2}-2y^{2}=8\) - step3: Simplify: \(2y^{2}+4y+1=8\) - step4: Move the expression to the left side: \(2y^{2}+4y+1-8=0\) - step5: Subtract the numbers: \(2y^{2}+4y-7=0\) - step6: Solve using the quadratic formula: \(y=\frac{-4\pm \sqrt{4^{2}-4\times 2\left(-7\right)}}{2\times 2}\) - step7: Simplify the expression: \(y=\frac{-4\pm \sqrt{4^{2}-4\times 2\left(-7\right)}}{4}\) - step8: Simplify the expression: \(y=\frac{-4\pm \sqrt{72}}{4}\) - step9: Simplify the expression: \(y=\frac{-4\pm 6\sqrt{2}}{4}\) - step10: Separate into possible cases: \(\begin{align}&y=\frac{-4+6\sqrt{2}}{4}\\&y=\frac{-4-6\sqrt{2}}{4}\end{align}\) - step11: Simplify the expression: \(\begin{align}&y=\frac{-2+3\sqrt{2}}{2}\\&y=\frac{-4-6\sqrt{2}}{4}\end{align}\) - step12: Simplify the expression: \(\begin{align}&y=\frac{-2+3\sqrt{2}}{2}\\&y=-\frac{2+3\sqrt{2}}{2}\end{align}\) - step13: Evaluate the logic: \(y=\frac{-2+3\sqrt{2}}{2}\cup y=-\frac{2+3\sqrt{2}}{2}\) - step14: Rearrange the terms: \(\left\{ \begin{array}{l}x=2y+1\\y=\frac{-2+3\sqrt{2}}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x=2y+1\\y=-\frac{2+3\sqrt{2}}{2}\end{array}\right.\) - step15: Calculate: \(\left\{ \begin{array}{l}x=-1+3\sqrt{2}\\y=\frac{-2+3\sqrt{2}}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x=-1-3\sqrt{2}\\y=-\frac{2+3\sqrt{2}}{2}\end{array}\right.\) - step16: Check the solution: \(\left\{ \begin{array}{l}x=-1+3\sqrt{2}\\y=\frac{-2+3\sqrt{2}}{2}\end{array}\right.\cup \left\{ \begin{array}{l}x=-1-3\sqrt{2}\\y=-\frac{2+3\sqrt{2}}{2}\end{array}\right.\) - step17: Rewrite: \(\left(x,y\right) = \left(-1+3\sqrt{2},\frac{-2+3\sqrt{2}}{2}\right)\cup \left(x,y\right) = \left(-1-3\sqrt{2},-\frac{2+3\sqrt{2}}{2}\right)\) Solve the system of equations \( y+6 x=4; y-x=-6 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y+6x=4\\y-x=-6\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=4-6x\\y-x=-6\end{array}\right.\) - step2: Substitute the value of \(y:\) \(4-6x-x=-6\) - step3: Subtract the terms: \(4-7x=-6\) - step4: Move the constant to the right side: \(-7x=-6-4\) - step5: Subtract the numbers: \(-7x=-10\) - step6: Change the signs: \(7x=10\) - step7: Divide both sides: \(\frac{7x}{7}=\frac{10}{7}\) - step8: Divide the numbers: \(x=\frac{10}{7}\) - step9: Substitute the value of \(x:\) \(y=4-6\times \frac{10}{7}\) - step10: Calculate: \(y=-\frac{32}{7}\) - step11: Calculate: \(\left\{ \begin{array}{l}x=\frac{10}{7}\\y=-\frac{32}{7}\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=\frac{10}{7}\\y=-\frac{32}{7}\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(\frac{10}{7},-\frac{32}{7}\right)\) Solve the system of equations \( 2 x-y=8; y=x^{2}+4 x-23 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2x-y=8\\y=x^{2}+4x-23\end{array}\right.\) - step1: Substitute the value of \(y:\) \(2x-\left(x^{2}+4x-23\right)=8\) - step2: Simplify: \(-2x-x^{2}+23=8\) - step3: Move the expression to the left side: \(-2x-x^{2}+23-8=0\) - step4: Subtract the numbers: \(-2x-x^{2}+15=0\) - step5: Factor the expression: \(\left(-x+3\right)\left(x+5\right)=0\) - step6: Separate into possible cases: \(\begin{align}&-x+3=0\\&x+5=0\end{align}\) - step7: Solve the equation: \(\begin{align}&x=3\\&x=-5\end{align}\) - step8: Calculate: \(x=3\cup x=-5\) - step9: Rearrange the terms: \(\left\{ \begin{array}{l}x=3\\y=x^{2}+4x-23\end{array}\right.\cup \left\{ \begin{array}{l}x=-5\\y=x^{2}+4x-23\end{array}\right.\) - step10: Calculate: \(\left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\cup \left\{ \begin{array}{l}x=-5\\y=-18\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=-5\\y=-18\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=-5\\y=-18\end{array}\right.\cup \left\{ \begin{array}{l}x=3\\y=-2\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(-5,-18\right)\cup \left(x,y\right) = \left(3,-2\right)\) Solve the system of equations \( y-2=2(x-1)^{2}; (x+5)^{2}+(y-3)^{2}=49 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y-2=2\left(x-1\right)^{2}\\\left(x+5\right)^{2}+\left(y-3\right)^{2}=49\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}y=2x^{2}-4x+4\\\left(x+5\right)^{2}+\left(y-3\right)^{2}=49\end{array}\right.\) - step2: Substitute the value of \(y:\) \(\left(x+5\right)^{2}+\left(2x^{2}-4x+4-3\right)^{2}=49\) - step3: Simplify: \(21x^{2}+2x+26+4x^{4}-16x^{3}=49\) - step4: Move the expression to the left side: \(21x^{2}+2x+26+4x^{4}-16x^{3}-49=0\) - step5: Subtract the numbers: \(21x^{2}+2x-23+4x^{4}-16x^{3}=0\) - step6: Calculate: \(x\approx 1.952466\cup x\approx -0.818491\) - step7: Rearrange the terms: \(\left\{ \begin{array}{l}x\approx 1.952466\\y=2x^{2}-4x+4\end{array}\right.\cup \left\{ \begin{array}{l}x\approx -0.818491\\y=2x^{2}-4x+4\end{array}\right.\) - step8: Calculate: \(\left\{ \begin{array}{l}x\approx 1.952466\\y\approx 3.814382\end{array}\right.\cup \left\{ \begin{array}{l}x\approx -0.818491\\y\approx 8.613821\end{array}\right.\) - step9: Calculate: \(\left\{ \begin{array}{l}x\approx -0.818491\\y\approx 8.613821\end{array}\right.\cup \left\{ \begin{array}{l}x\approx 1.952466\\y\approx 3.814382\end{array}\right.\) - step10: Check the solution: \(\left\{ \begin{array}{l}x\approx -0.818491\\y\approx 8.613821\end{array}\right.\cup \left\{ \begin{array}{l}x\approx 1.952466\\y\approx 3.814382\end{array}\right.\) - step11: Rewrite: \(\left(x,y\right)\approx \left(-0.818491,8.613821\right)\cup \left(x,y\right)\approx \left(1.952466,3.814382\right)\) Solve the system of equations \( 2 x-3 y=2; x^{2}+2 x y-2 x-4 y=0 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2x-3y=2\\x^{2}+2xy-2x-4y=0\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{2+3y}{2}\\x^{2}+2xy-2x-4y=0\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left(\frac{2+3y}{2}\right)^{2}+2\times \frac{2+3y}{2}\times y-2\times \frac{2+3y}{2}-4y=0\) - step3: Simplify: \(-1-2y+\frac{21}{4}y^{2}=0\) - step4: Factor the expression: \(\frac{1}{4}\left(-2+3y\right)\left(2+7y\right)=0\) - step5: Divide the terms: \(\left(-2+3y\right)\left(2+7y\right)=0\) - step6: Separate into possible cases: \(\begin{align}&-2+3y=0\\&2+7y=0\end{align}\) - step7: Solve the equation: \(\begin{align}&y=\frac{2}{3}\\&y=-\frac{2}{7}\end{align}\) - step8: Calculate: \(y=\frac{2}{3}\cup y=-\frac{2}{7}\) - step9: Rearrange the terms: \(\left\{ \begin{array}{l}x=\frac{2+3y}{2}\\y=\frac{2}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{2+3y}{2}\\y=-\frac{2}{7}\end{array}\right.\) - step10: Calculate: \(\left\{ \begin{array}{l}x=2\\y=\frac{2}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{4}{7}\\y=-\frac{2}{7}\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=2\\y=\frac{2}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{4}{7}\\y=-\frac{2}{7}\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(2,\frac{2}{3}\right)\cup \left(x,y\right) = \left(\frac{4}{7},-\frac{2}{7}\right)\) Solve the system of equations \( y-x=5; 2 x^{2}+5 x y=-2 y^{2} \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}y-x=5\\2x^{2}+5xy=-2y^{2}\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-5+y\\2x^{2}+5xy=-2y^{2}\end{array}\right.\) - step2: Substitute the value of \(x:\) \(2\left(-5+y\right)^{2}+5\left(-5+y\right)y=-2y^{2}\) - step3: Simplify: \(50-45y+7y^{2}=-2y^{2}\) - step4: Move the expression to the left side: \(50-45y+7y^{2}-\left(-2y^{2}\right)=0\) - step5: Calculate: \(50-45y+9y^{2}=0\) - step6: Factor the expression: \(\left(10-3y\right)\left(5-3y\right)=0\) - step7: Separate into possible cases: \(\begin{align}&10-3y=0\\&5-3y=0\end{align}\) - step8: Solve the equation: \(\begin{align}&y=\frac{10}{3}\\&y=\frac{5}{3}\end{align}\) - step9: Calculate: \(y=\frac{10}{3}\cup y=\frac{5}{3}\) - step10: Rearrange the terms: \(\left\{ \begin{array}{l}x=-5+y\\y=\frac{10}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=-5+y\\y=\frac{5}{3}\end{array}\right.\) - step11: Calculate: \(\left\{ \begin{array}{l}x=-\frac{5}{3}\\y=\frac{10}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{10}{3}\\y=\frac{5}{3}\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-\frac{10}{3}\\y=\frac{5}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{5}{3}\\y=\frac{10}{3}\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{10}{3}\\y=\frac{5}{3}\end{array}\right.\cup \left\{ \begin{array}{l}x=-\frac{5}{3}\\y=\frac{10}{3}\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-\frac{10}{3},\frac{5}{3}\right)\cup \left(x,y\right) = \left(-\frac{5}{3},\frac{10}{3}\right)\) Here are the solutions for each of the simultaneous equations provided: ### a) Equations: 1. \( y + 6x = 4 \) 2. \( y - x = -6 \) **Solution:** \[ (x,y) = \left(\frac{10}{7}, -\frac{32}{7}\right) \] ### b) Equations: 1. \( 2x - y = 8 \) 2. \( y = x^2 + 4x - 23 \) **Solution:** \[ (x,y) = (-5,-18) \cup (x,y) = (3,-2) \] ### c) Equations: 1. \( y - x = 5 \) 2. \( 2x^2 + 5xy = -2y^2 \) **Solution:** \[ (x,y) = \left(-\frac{10}{3}, \frac{5}{3}\right) \cup (x,y) = \left(-\frac{5}{3}, \frac{10}{3}\right) \] ### d) Equations: 1. \( y + x = 6 \) 2. \( 2^{x+y} = 256 \) **Solution:** \[ (x, y) \in \varnothing \quad \text{(No solution)} \] ### e) Equations: 1. \( 2x - 3y = 2 \) 2. \( x^2 + 2xy - 2x - 4y = 0 \) **Solution:** \[ (x,y) = (2,\frac{2}{3}) \cup (x,y) = \left(\frac{4}{7}, -\frac{2}{7}\right) \] ### f) Equations: 1. \( y - 2 = 2(x - 1)^2 \) 2. \( (x + 5)^2 + (y - 3)^2 = 49 \) **Solution:** \[ (x,y) \approx (-0.818491, 8.613821) \cup (x,y) \approx (1.952466, 3.814382) \] ### g) Equations: 1. \( y - x = 2 \) 2. \( y + x = -9 \) **Solution:** \[ (x,y) = \left(-\frac{11}{2}, -\frac{7}{2}\right) \] ### h) Equations: 1. \( 5^{x - 2y - 1} = 1 \) 2. \( x^2 - 2y^2 = 8 \) **Solution:** \[ (x,y) = \left(-1 + 3\sqrt{2}, \frac{-2 + 3\sqrt{2}}{2}\right) \cup (x,y) = \left(-1 - 3\sqrt{2}, -\frac{2 + 3\sqrt{2}}{2}\right) \] These solutions provide the values of \( x \) and \( y \) for each pair of equations. If you need further clarification or additional problems solved, feel free to ask!

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

Step back into the world of mathematics, where simultaneous equations have been whispering problems into the ears of curious minds for ages! Did you know that the method of substitution and elimination used to solve these equations has been around since ancient times? Even mathematicians like Isaac Newton and René Descartes dabbled in them! Their tactics have paved the way for modern algebra and have implications in fields from physics to economics. To tackle the exercise at hand, remember that a common pitfall is failing to keep track of signs especially when rearranging equations! It’s helpful to carefully label each step and double-check your arithmetic. Additionally, trying different methods like graphing or using matrices can provide a clearer picture of the solutions you’re nearing—plus, it can turn solving these equations into a bit of an adventure!

preguntas relacionadas

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Álgebra Mexico Feb 26, 2025
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad